Invited to know God the book of Deuteronomy - Culp, A. J. (Ashland Lexham Press, 2019)
Intro -- Title Page -- Copyright -- Dedication -- Table of Contents -- 1. A Lens for Reading -- Reflection -- 2. Introducing Deuteronomy -- Deuteronomy as Sermon -- Deuteronomy as Treaty -- Goodness like a Fetter -- Reflection -- 3. Deuteronomy 1-4: Memory as a Means of Knowing God -- On the Road -- Joining the Journey -- Knowing God through Memory -- Reflection -- 4. Deuteronomy 5-11: Worship as a Means of Knowing God -- The Face in the Pool -- Worship as Prioritizing -- Worship as Adoring -- Worship as Beholding -- Knowing God through Worship -- Reflection -- 5. Deuteronomy 12-26: Law as a Means of Knowing God -- Knowing through Doing -- The Law: A Tutor in Gratefulness -- Knowing God through Obedience -- Reflection -- 6. Deuteronomy 27-34: Covenant as a Means of Knowing God -- Knowing through Commitment -- Covenant: An Environment for Learning -- Knowing God through Covenant -- Reflection -- 7. Jesus and Deuteronomy: Grace as a Means of Knowing God -- A Deeper Magic -- Deuteronomy and a Deeper Magic -- Knowing God through the New Covenant -- Reflection -- Concluding Thoughts -- Reflection -- Recommended Reading.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Deuteronomy-Commentaries; Electronic books